Evolution of pandemic cholera at its global source - Amber Barton; Mokibul Hassan Afrad; Alyce Taylor-Brown; Nisha Singh; Chetan Thakur; Taufiqul Islam; Sadia Isfat Ara Rahman; Marjahan Akhtar; Yasmin Ara Begum; Taufiqur Rahman Bhuiyan; Ashraful Islam Khan; Neelam Taneja; et al. (Nature, 2026)
Abstract The seventh pandemic of cholera, caused by the seventh pandemic El Tor lineage of Vibrio cholerae , was previously shown to have emanated in three global waves from the Bay of Bengal, bordering Bangladesh and India 1 . However, the respective roles of the Ganges Delta and Basin regions in seeding these global pandemic waves were not known. Here we show that, although transmission events occur between Bangladesh and India, V. cholerae in the two countries has largely evolved separately over the past 20 years, apparently constrained by national borders rather than by hydrological features, such as the Ganges Delta and Basin. Evolution within Bangladesh was distinct from that seen in India, involving rapid gain and loss of genes and mobile genetic elements, particularly those involved in phage defence. The loss of these systems was associated with increased risk of severe disease and transmission outside Bangladesh. Lineage replacement in Bangladesh in 2018, resulting in a major change in phage defence systems, was accompanied by a rapid change in the lineage and anti-defence system of lytic phage ICP1. Here we show that the Ganges Basin, falling across Bangladesh and Northern India, rather than the Ganges Delta, probably acts as a global launch pad for pandemic disease. This shifts our understanding of Bangladesh as the purported global source of cholera and underscores the potential role of phage in controlling spread of lineages within the current seventh pandemic.